2012
DOI: 10.1210/jc.2012-1190
|View full text |Cite
|
Sign up to set email alerts
|

Hyperglycemic Chorea-Ballism or Acute Exacerbation of Huntington's Chorea? Huntington's Disease Unmasked by Diabetic Ketoacidosis in Type 1 Diabetes Mellitus

Abstract: The present case provides important insights on the role of GABA in hyperglycemic chorea-ballism and on the clinical issues associated with HD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…The pathogenesis of diabetic striatopathy remains unclear, and the present case has important implications. To date, possible mechanisms reported include microhaemorrhage [16,17], reactive astrocytes associated with ischaemia [18,19], and metabolic disorder with decreased caminobutyric acid production [20,21]. In the present case, magnetic resonance angiography illustrated oozing around the basal ganglia, which is similar to the results of previous reports [22] in which vascular injury was suspected.…”
supporting
confidence: 85%
“…The pathogenesis of diabetic striatopathy remains unclear, and the present case has important implications. To date, possible mechanisms reported include microhaemorrhage [16,17], reactive astrocytes associated with ischaemia [18,19], and metabolic disorder with decreased caminobutyric acid production [20,21]. In the present case, magnetic resonance angiography illustrated oozing around the basal ganglia, which is similar to the results of previous reports [22] in which vascular injury was suspected.…”
supporting
confidence: 85%
“…DHC-HB is also related to insufficient inhibition from the internal segment of the globus pallidus to the thalamus, reportedly due to the depletion of gamma-aminobutyric acid (8). However, other studies have shown that dopaminergic hyperactivity is involved in hemichorea and hemiballism of other etiologies (9).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia and/or metabolic acidosis produces a decrease in regional cerebral blood flow with maximal reduction in basal ganglia resulting in ischaemia 5. Hyperglycaemia shifts cellular energy demands towards anaerobic metabolism which causes increased metabolism of gamma amino butyric acid (GABA) in the brain as an alternate energy source resulting in depletion of the GABA content in basal ganglia, decreasing inhibitory signals and causing involuntary movements 5. In ketoacidotic state acetoacetate may be used to synthesise GABA which may explain the rarity of this condition in patients with diabetic ketocidosis and type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%